Effects of 18-month vildagliptin treatment on portal vein pressure and hepatosteatosis - Karatoprak, Cumali; Kılıçarslan, Rukiye; Çakırca, Mustafa; Aydın, Sinem; Özkan, Tuba; Zorlu, Mehmet; Kıskaç, Muhammet (Bezmialem Vakif University, 2019)
Objective: Patients with type 2 diabetes have an increased tendency to develop hepatosteatosis. The effects of drugs used to treat diabetes on the liver, regardless of the disease, are unknown.The aim of this study was to investigate the effects of vildagliptin, a dipeptidyl peptidase-4 inhibitor, on the portal vein pressure and hepatosteatosis in patients with type 2 diabetes in the 18 months of follow-up. Methods: Patients to whose treatment vildagliptin was added while they were on therapy with metformin and gliclazide for type 2 DM the vildagliptin group were included. As the control group, 49 patients with type 2 DM treated with metformin and gliclazide were included. These patients were followed up for 18 months. These patients were followed for 18 months and their pre-treatment and post-treatment examinations were repeated. Portal vein diameter, portal vein flow and portal vein velocity were calculated to evaluate portal vein pressure with the same Doppler ultrasonography (US) by the same radiologist. In the same session, the liver steatosis stage of all patients was evaluated with US and recorded. The data before treatment and the data 18 months after treatment were compared. Results: Nineteen patients completed the study in the study group, while 10 patients completed the study in the control group. A significant increase in portal vein flow velocity and vein diameter was found in the study group when portal vein parameters were compared before and after treatment (p=<0.001, p=0.035, respectively). There was no significant difference in portal vein flow volume. In the control group, no significant changes in flow velocity and flow volume were detected, although there was a significant increase in portal vein diameter (p=0.04, p=0.07, p=0.14, respectively). There were no significant changes in vildagliptin group before and after treatment in terms of hepatosteatosis (p=0.41). There were no significant changes between control and study groups in terms of hepatosteatosis after 18 months of treatment. Conclusion: As a result, we did not find any significant changes in the parameters of portal vein pressure with vildagliptin use. We think that vildagliptin has no effect on hepatosteatosis.
Keywords: Di-Peptidyl Peptidase 4 Inhibitors; Vildagliptin; Portal Vein Pressure; Hepatosteatosis; Tip 2 Diabetes Mellitus